The Relative and Incremental Explanatory Power of Earnings and Alternative (to Earnings) Performance Measures for Returns* - Francis, Jennifer; Schipper, Katherine; Vincent, Linda (Contemporary Accounting Research, 2003)
We analyze the ability of earnings and non‐earnings performance metrics to explain the variability in annual stock returns for industries where we identify, ex ante, an allegedly preferred (for valuation purposes) summary performance metric. We identify three industries where earnings before interest, taxes, depreciation, and amortization (EBITDA) and cash from operations (CFO) are preferred, and three industries where specific non‐GAAP performance metrics are preferred. As a benchmark, we also examine the ability of EBITDA and CFO to explain returns for seven industries for which earnings is the preferred metric. Results for the benchmark earnings industries show that earnings dominates EBITDA and CFO in explaining returns. All other results are inconsistent with the view that perceptions of preferred metrics are reflected in actual aggregate investment behaviors.